Energy landscapes reveal the myopathic effects of tropomyosin mutations - Orzechowski, Marek; Fischer, Stefan (Archives of biochemistry and biophysics, 2014)
Striated muscle contraction is regulated by an interaction network connecting the effects of troponin, Ca2+, and myosin-heads to the azimuthal positioning of tropomyosin along thin filaments. Many missense mutations, located at the actin-tropomyosin interface, however, reset the regulatory switching mechanism either by weakening or strengthening residue-specific interactions, leading to hyper- or hypo-contractile pathologies. Here, we compute energy landscapes for the actin-tropomyosin interface and quantify contributions of single amino acid residues to actin-tropomyosin binding. The method is a useful tool to assess effects of actin and tropomyosin mutations, potentially relating initial stages of myopathy to alterations in thin filament stability and regulation. Landscapes for mutant filaments linked to hyper-contractility provide a simple picture that describes a decrease in actin-tropomyosin interaction energy. Destabilizing the blocked (relaxed)-state parallels previously noted enhanced Ca2+-sensitivity conferred by these mutants. Energy landscapes also identify post-translational modifications that can rescue regulatory imbalances. For example, cardiomyopathy-associated E62Q tropomyosin mutation weakens actin-tropomyosin interaction, but phosphorylation of neighboring S61 rescues the binding-deficit, results confirmed experimentally by in vitro motility assays. Unlike results on hyper-contractility-related mutants, landscapes for tropomyosin mutants tied to hypo-contractility do not present a straightforward picture. These mutations may affect other components of the regulatory network, e.g., troponin-tropomyosin signaling.